2018
DOI: 10.3389/fpls.2018.01263
|View full text |Cite
|
Sign up to set email alerts
|

TCP Transcription Factors in Moso Bamboo (Phyllostachys edulis): Genome-Wide Identification and Expression Analysis

Abstract: TEOSINTE BRANCHED 1, CYCLOIDEA, and PROLIFERATING CELL FACTORS (T), members of a plant-specific gene family, play significant roles during plant growth and development, as well as in response to environmental stress. However, knowledge about this family in moso bamboo (Phyllostachys edulis) is limited. Therefore, in this study, the first genome-wide identification, classification, characterization, and expression pattern analysis of the TCP transcription factor family in moso bamboo was performed. Sixteen TCP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 76 publications
5
37
0
Order By: Relevance
“…Moreover, bamboo is known for its fast-growing shoots and widespread rhizomes [2]. It has been reported that several gene families are involved in flower development and abiotic stress [30][31][32]37]; however, the rapid-growth associated transcription factors remain elusive. The genome sequences of moso bamboo [36] and transcriptome studies [2,27,28,34] provide important platforms for the identification of rapid-growth shoot and rhizome development associated gene families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, bamboo is known for its fast-growing shoots and widespread rhizomes [2]. It has been reported that several gene families are involved in flower development and abiotic stress [30][31][32]37]; however, the rapid-growth associated transcription factors remain elusive. The genome sequences of moso bamboo [36] and transcriptome studies [2,27,28,34] provide important platforms for the identification of rapid-growth shoot and rhizome development associated gene families.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, large-scale transcriptome analysis has shown that light and phytohormones may play important roles in the rapid-growth of bamboo [27][28][29]. In addition, a large number of transcription factor families, involved in the abiotic stress response and flower development, have been studied in moso bamboo [30][31][32]. Although a previous study has functionally characterized the rapid-growth associated gene-PeGSK1 [1], the rapid-growth associated transcription factor families are largely unexplored in moso bamboo.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bamboo is known for its fast-growing shoots and widespread rhizomes [2]. It has been reported that several gene families are involved in flower development and abiotic stress [3032, 41], the rapid-growth associated transcription factors remain elusive. The genome sequences of moso bamboo[33] and transcriptome studies [2, 27, 28, 40] provide important platforms for the identification of rapid-growth shoot and rhizome development associated gene families.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, large-scale transcriptome analysis has shown that light and phytohormones may play important roles in the rapid-growth of bamboo [2729]. In addition, a large number of transcription factor families are involved in the abiotic stress response and flower development have been studied in moso bamboo [3032]. Although our group has functionally characterized rapid-growth associated key gene- PeGSK1 , the rapid-growth associated transcription factor families are largely unexplored in moso bamboo.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of TCP family members have been characterized in both dicots and monocots with the completion of entire genome, such as Arabidopsis [32], tomato [21], apple [33], strawberry [31], bamboo [34] and switchgrass [35]. However, little is known about the TCP family in grapevine [36], which is one of the most important fruit crop growing around the world with great nutritive and commercial value [37][38][39].…”
Section: Introductionmentioning
confidence: 99%